Impact of the COVID-19 pandemic on radiology appointments in a tertiary children's hospital: a retrospective study - Mario Cortina-Borja; Andrew Taylor; Neil J Sebire; Susan Shelmerdine; Dean Langan; Owen Arthurs; John Booth; William A Bryant (BMJ Publishing Group, 2021)
In this retrospective observational study, we evaluated the impact of the COVID-19 pandemic in London on paediatric radiology activity, as a surrogate of overall hospital activity. We showed a large reduction in overall outpatient imaging activity: 49 250 records occurred in the 371 days post COVID-19 period compared with an expected 67 806 records pre COVID-19 period, representing 18 556 'missed' records. Governmental restrictions were associated with reductions in activity, with the largest reduction in activity during tiers 3 and 4 restrictions. Rescheduling such missed outpatients' appointments represents considerable resource planning and the associated clinical impact on paediatric healthcare remains to be determined.